Legal Analysis of Protection Against Breach of Employment Contract - Asri, Muhammad Rozi; Marsal, Irsyaf (Dinasti Research, 2025)
This study aims to analyze the forms of default (breach of contract) committed by the government as the employer in the implementation of the Work Order (SPK) and to examine the legal remedies available for contractors to obtain legal protection. This research employs a normative juridical method using statute, case, and conceptual approaches. The legal materials used include primary, secondary, and tertiary sources, analyzed qualitatively through a descriptive-analytical technique. The results indicate that government default commonly occurs in the form of delayed payments, unilateral changes to the scope of work, and contract termination without legal justification. These actions cause losses to contractors due to their weak bargaining position in legal relations with the government. Legal protection for contractors can be pursued through warnings (somasi), civil lawsuits based on Articles 1243–1252 of the Indonesian Civil Code, and non-litigation dispute resolution mechanisms such as mediation or arbitration as regulated under Law Number 2 of 2017 on Construction Services and Presidential Regulation Number 16 of 2018 on Government Procurement of Goods/Services. This study emphasizes the need to strengthen regulations and improve dispute resolution mechanisms to ensure legal certainty and fairness for contractors in the implementation of work orders.